Os elementos visuais do espetáculo no processo criativo do ator - Luiz Renato Gomes Moura (2019)
The object of this research is the problematization of the possible relations among the creative process of the actor and the visual elements of the spectacle. The reflections are the result of the perception and experience of the researcher, as an actor in the Cia. de Teatro Engenharia Cênica. The conceptual investigations that constituted the research are based on theoretical references that discuss the scene,the work of actor and the visual elements of the spectacle, especially the light design, scenography, costumes and makeup. Based on this study, principles and strategies have been created that can provide dialogues between the visual elements and the actor, in the genesis of creating the scene. With this thesis, the author intends to contribute to broadening the studies on the visual elements of the spectacle, especially the relations that can be established for the deepening of the researches on the creative process of actor.